Ethical issues related to eHealth: An integrative review - Jokinen, Anu (Nursing ethics, 2021)
Background:Identifying and safeguarding ethics in eHealth services from the service users? perspective in social care and healthcare is important. The use of eHealth services should not prejudice the quality of services or the social interaction required in care. There is a lack of studies about the ethics of eHealth services from the service users? perspective.Aim:The aim of this study is to identify and analyse ethical issues related to eHealth in social care and healthcare from the service users? perspective.Research design:An integrative literature review.Ethical considerations:The review followed good scientific conduct.Research context and data sources:A systematic literature search was performed using CINAHL, Scopus, PubMed/MEDLINE, Web of Science, Cochrane Library and Academic Search Premier to find relevant empirical studies published in English from their earliest up to 30 November 2018. In addition, reference lists from the identified research papers were searched. A quality appraisal of each paper included in the review was conducted before thematic analysis.Results:In total, 26 studies were included in the review, and from these four ethical themes were identified: (1) privacy in eHealth, (2) beneficence and nonmaleficence in eHealth, (3) justice in eHealth and (4) trust in eHealth. The ethical issues within these themes were related to information sharing; ownership; access to information and data protection; informed consent; defence of rights; and equity, equality and proportionality of response.Conclusion:eHealth inequality occurs in social care and healthcare. eHealth service designers and social care and healthcare professionals need to act to maintain and improve user access and data accuracy and provide different levels of security in eHealth services, relative to the information stored. There is a need for further research about ethical issues of eHealth from the user?s perspective, including the customer-oriented availability and usability of eHealth services which avoid discrimination.